Analysis of Risk Factors of Chronic Kidney Disease on Patients With Hemodialysis in Tangerang District Hospital (Jurnal Ilmu Kesehatan Masyarakat, 2019)
Chronic kidney disease (CKD) is a major world health challenge in the 21st centuries. The prevalence of CKD in Indonesia based on the doctor's diagnosis is 0.2% while for Tangerang prevalence at 0.1%. There are no clear data of the predisposing factor of CKD in Banten province, especially in Tangerang. The purpose of this study was to analyze the risk factors CKD on patients with hemodialysis in Tangerang District Hospital. This study is an observational analytic research with case-control and cross sectional approach conducted in August to September 2017 at the Tangerang District Hospital. with 70 respondents in case group and 70 respondents in control group. The result of the bivariate analysis showed that 15 of 19 risk factors significantly (p ≤ 0.05) increased the risk of CKD with OR range 2,043 to 4,235. The result of multivariate analysis with logistic regression test showed that the most dominant risk factor for CKD was hypertension with OR 21,806 (95% C.I. 1,015- 486,554) and p = 0,049. There are 15 risk factors that could increase the risk of CKD. the most dominant risk factor for CKD was hypertension